The ‘Oath of Philippus’ and the Di Indigetes - Rose, Herbert Jennings (Harvard theological review, 1937)
In the course of a valuable discussion of the Di Indigetes, Koch seeks to prove that the epithet means Stammväter, using as his material certain passages of Greek authors which seem to equate indiges with γενάρχης. Of these the chief is the famous fragment of Diodorus Siculus preserved in a Vatican MS. and first published by Mai, Scriptorum Veterum Noua Collectio, ii, p. 116.